Passivation and Annealing for Improved Stability of High Performance IGZO TFTs. Issue 1692 (14th October 2014) - Mudgal, T.; Walsh, N.; Manley, R.G.; Hirschman, K.D.
ABSTRACT: The influence of annealing ambient conditions and deposited passivation materials on indium-gallium-zinc-oxide (IGZO) thin-film transistor (TFT) performance is investigated. Results from annealing experiments confirm that a nominal exposure to oxidizing ambient conditions is required, which is a function of temperature, time and gas environment. Nitrogen anneal with a controlled air ramp-down provided the best performance devices with a mobility (µsat ) of 11-13 cm 2 /V·s and subthreshold slope (SS) of 135-200 mV/dec, with some hysteresis. Plasma-deposited passivation materials including sputtered quartz and PECVD SiO2 demonstrated a significant increase in material conductivity, which was not significantly reversible by an oxidizing ambient anneal. E-beam evaporated Al2 O3 passivated devices that were annealed in air at 400 °C demonstrated improved stability over time and suppressed hysteresis in comparison to unpassivated devices. Devices which were passivated with B-staged bisbenzocyclobutene-based (BCB) resins and annealed in air at 250 °C also exhibited suppressed hysteresis.